HOW TO TEACH CAD SYSTEM? - SOTAK, Vladimir; KUNIK, Martin; SOTAK, Robert (Journal of Technology and Information Education, 2011)
The contribution deals with selected issues from the area of teaching CAD/CAM systems, particularly AutoCAD. It consists of a part called the methodical guide book on teaching AutoCAD and the proposal for time-content plan of teaching. In the process of teaching we emphasize fundamental didactical principles, especially those of succession and visualization.
Keywords: CAD; CAM; AutoCAD; computer skills; software support; programming; educational standards; teaching process